Personality in politics : studies of contemporary statesmen - Salter, Arthur (London : Faber and Faber, 1947)
Bibliotheek Camille Huysmans
Dedicator: Salter, Arhtur, dedicatee: Huysmans, Camille
Engels
Monografie
Keywords: politieke figuren; Wereldoorlog 2